Cyclooxygenase-2 Facilitates Newcastle Disease Virus Proliferation and Is as a Target for Canthin-6-One Antiviral Activity - Wang, Chongyang; Wang, Ting; Hu, Ruochen; Dai, Jiangkun; Liu, Haijin; Li, Na; Schneider, Uwe; Yang, Zengqi; Wang, Junru (Frontiers in Microbiology, 2020)
Cyclooxygenase-2 (COX-2), one of the mediators of inflammation in response to viral infection, plays an important role in host antiviral defense system. But its role in Newcastle disease virus (NDV) proliferation process remains unclear. This study revealed that inhibition of COX-2 could benefit NDV proliferation and overexpression of COX-2 dose-dependently suppressed NDV proliferation. Overexpression of COX-2 also showed inhibitory effect on NDV-induced endoplasmic reticulum (ER)-stress and autophagy, also promoted the expression of antiviral genes. However, prostaglandin E2 (PGE2), the major product of COX-2, had indistinctive effects on NDV proliferation. At variant time point post viral infection, a tight regulation pattern of COX-2 by NDV was observed. Using inhibitors and siRNA against signaling molecules, the nuclear factor-κB (NF-κB) and melanoma differentiation-associated gene 5 (MDA5) were identified as critical factors for NDV induced COX-2 expression. Nonetheless, at late stage of NDV proliferation, substantial suppression of COX-2 protein synthesis could be detected, accompanied by a decrease in mRNA half-life. Furthermore, three C ring-truncated canthin-6-one analogues were used to activate COX-2 expression and showed inhibitory effect on NDV proliferation with the effective concentrations on μM level. Taken together, these results illustrated a novel NDV-regulated cellular mechanism and indicated that COX-2 is an important regulator of NDV proliferation which can serve as a potential target for anti-NDV agents.